C‐Jun N‐terminal kinase mediates mouse liver injury through a novel Sab (SH3BP5)‐dependent pathway leading to inactivation of intramitochondrial Src. Issue 6 (15th March 2016) - Win, Sanda; Than, Tin Aung; Min, Robert Win Maw; Aghajan, Mariam; Kaplowitz, Neil
Abstract : Sustained c‐Jun N‐terminal kinase (JNK) activation has been implicated in many models of cell death and tissue injury. Phosphorylated JNK (p‐JNK) interacts with the mitochondrial outer membrane SH3 homology associated BTK binding protein (Sab, or SH3BP5). Using knockdown or liver‐specific deletion of Sab, we aimed to elucidate the consequences of this interaction on mitochondrial function in isolated mitochondria and liver injury models in vivo . Respiration in isolated mitochondria was directly inhibited by p‐JNK + adenosine triphosphate. Knockdown or liver‐specific knockout of Sab abrogated this effect and markedly inhibited sustained JNK activation and liver injury from acetaminophen or tumor necrosis factor/galactosamine. We then elucidated an intramitochondrial pathway in which interaction of JNK and Sab on the outside of the mitochondria released protein tyrosine phosphatase, nonreceptor type 6 (SHP1, or PTPN6) from Sab in the inside of the mitochondrial outer membrane, leading to its activation and transfer to the inner membrane, where it dephosphorylates P‐Y419Src (active), which required a platform protein, docking protein 4 (DOK4), on the inner membrane. Knockdown of mitochondrial DOK4 or SHP1 inhibited the inactivation of mitochondrial p‐Src and the effect of p‐JNK on mitochondria. Conclusions: The binding to and phosphorylation of Sab by p‐JNK on the outer mitochondrial membrane leads to SHP1‐dependent and DOK4‐dependent inactivation of p‐Src on the inner membrane; inactivation of mitochondrial Src inhibits electron transport and increases reactive oxygen species release, which sustains JNK activation and promotes cell death and organ injury. (Hepatology 2016;63:1987‐2003)